Renewable energy policy: Risk hedging is taking center stage - Nils May; Ingmar Jürgens; Karsten Neuhoff (DIW Economic Bulletin, 2017)
The costs of renewable energy technologies have fallen sharply. Now the financing costs of new installations are playing an increasing role in the overall cost of Germany's energy transition. This has put the primary focus of support instruments for renewable energy on creating more affordable financing conditions for investments. This report compares the effects of various policy instruments on risk factors and on the costs of financing investment in the energy transition. Based on a survey evaluation and calculations, our analysis shows significant increases in the financing costs under green certificates and fixed premiums. These are passed on to end customers. For this reason, the further development of support instruments, as currently discussed within the context of the EU Renewable Energy Directive for the period 2020-2030, should avoid unnecessary risks for investors that could lead to higher financing costs.
Keywords: Q42; Q55; O38; 330; investments; long-term contracts; financing costs; renewable energy policies